PENGARUH HARGA DAN KUALITAS PRODUK TEHADAP KEPUTUSAN PEMBELIAN MAHASISWA SUNAN DOE DI APLIKASI SHOPEE - Wahyudi, Zaenul; Amrullah, Amdi (Politeknik Negeri Lhokseumawe, 2025)
Abstract: The purpose of this study is to determine the extent to which price and product quality influence the purchasing decisions of students at the Sunan Drajat Islamic Studies Institute on the Shopee application. The research method used in this study is descriptive quantitative research. The analysis method used in this study is multiple linear regression analysis and the coefficient of determination test to determine the extent to which price and product quality influence purchasing decisions. The results of the hypothesis testing in this study lead to the conclusion that from the T-test or partial test, the price and product quality influence purchasing decisions on the Shopee application among Sunan Doe students. This is evidenced by a calculated T-value greater than the T-table value, with a significance level greater than 0.05. Simultaneously, based on the results of the F-test, it was found that price and product quality influence purchasing decisions on the Shopee application, as evidenced by an F-value of 55.925, which is greater than the F-table value of 3.11, and a significance level of 0.000, which is less than 0.05. From the results of the coefficient of determination analysis (R2), it was found that the price variable has a partial influence of 12.1%, while product quality has an influence of 53.3%. Simultaneously, price and product quality have an influence of 57.6% on purchasing decisions on the Shopee application among Sunan Doe students, while the remaining 42.4% is influenced by other variables outside of this study. Keywords: : Price, Quality, Product, Decision, Purchase